Varied presentations of progressive familial intrahepatic cholestasis Type 2 in infancy: A report of two cases - Deswal, Shivani; Singh, Hemlata; Dey, Soumya; Yadav, T P (Indian Journal of Case Reports, 2020)
Progressive familial intrahepatic cholestasis (PFIC) is a genetic disorder presenting in children with cholestasis. Type 2 known as bile salt export pump (BSEP) deficiency involves ABCB11 gene mutation leading to BSEP defect causing accumulation of bile salts within canaliculi and eventually hepatocellular injury. Disease hallmarks are jaundice, pruritus, and poor growth. We report varied presentations in 10-month old infants. First unusual presentation mimicked viral hepatitis without pruritus and growth failure and second, presenting classically with coagulopathy, pruritus, jaundice, and failure to thrive. Diagnosis of PFIC may be missed in absence of disease hallmark of pruritus and early biopsy with immunohistochemistry can change the outcome.